The moderating effect of care time on care-related characteristics and caregiver burden: differences between formal and informal caregivers of dependent older adults - Oh, Eunmi; Moon, SeolHwa; Chung, Daum; Choi, Rina; Hong, Gwi-Ryung Son (Frontiers in Public Health, 2024)
Objective This study examined differences in care burden between formal and informal caregivers of dependent older adults according to care-related characteristics, and whether care time had a moderating effect on the relationship between care-related characteristics and caregiver burden. Methods Participants were formal (n = 520) and informal caregivers (n = 142) of dependent older adults in South Korea. Caregiver burden was measured using the Korean version of the Zarit Burden Interview. Data were analyzed using hierarchical regression with interaction terms and moderation analysis. Results Caregiver burden was higher for informal caregivers than formal caregivers. Factors associated with an increased risk of caregiver burden in both formal and informal caregiver of dependent older adults were caregivers’ stress, physical strain, and care time. Care time significantly moderated the relationship between care attitude and care burden only among formal caregivers. When formal caregivers’ care time was 1 standard deviation higher than the mean value, care attitude was significantly associated with care burden (bsimple = −0.903, SE = 0.106, p < 0.001). Conclusion The caregiver burden of dependent older adults can be reduced by providing interventions to attenuate the effects of modifiable risk factors that were identified in this study. And to weaken the relationship between care attitude and burden of formal caregivers who have long care hours, a positive social atmosphere for care should be provided in addition to education. To realize sustainable care, policy considerations that reflect the results of this study will help solve the problem of formal and informal caregiver burden of dependent older adults.